Women and terrorism female activity in domestic and international terror groups - Gonzalez-Perez, Margaret (Contemporay terrorism studies., 2008)
Examines the relationship between women and terrorist activities in the post-World War II era. This work identifies a dichotomy whereby women are significantly more active in domestic terrorist organizations than in international groups.